2021
DOI: 10.1039/d1ob01677f
|View full text |Cite
|
Sign up to set email alerts
|

Chemical catalyst-promoted photooxygenation of amyloid proteins

Abstract: Misfolded proteins produce aberrant fibrillar aggregates, called amyloid, that contain cross-beta-sheet higher order structures. The species generated in the aggregation processes (i.e., oligomers, protofibrils, and fibrils) are cytotoxic and can...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Photooxygenation of histidine in undruggable protein targets, specifically amyloids, has been realized by our group – [26 –28] . Amyloids are insoluble fibrillar structures that arise from the abnormal aggregation of proteins or peptides.…”
Section: Application Of Histidine Photooxygenationmentioning
confidence: 99%
“…Photooxygenation of histidine in undruggable protein targets, specifically amyloids, has been realized by our group – [26 –28] . Amyloids are insoluble fibrillar structures that arise from the abnormal aggregation of proteins or peptides.…”
Section: Application Of Histidine Photooxygenationmentioning
confidence: 99%
“…Aggregated Aβ as well as tau contains the cross-β-sheet structure and is called amyloid. Targeting the cross-β-sheet structure characteristic of amyloids, we developed Aβ amyloid-selective photo-oxygenation catalysts 1–4 (Figure a). Only when interacting with the cross-β-sheet structure do these catalysts get activated and act as photosensitizers to generate singlet oxygen ( 1 O 2 ) under light irradiation. Due both to the switch function of the catalysts and the short-lived nature of 1 O 2 , photo-oxygenation proceeds selectively with amyloids. Specifically, histidine (His) and methionine (Met) were the main oxygenation sites using catalysts 1–4 . , The covalent incorporation of hydrophilic oxygen atoms into the amyloid decreased its aggregative property and facilitated phagocytotic degradation of Aβ amyloid by microglia cells in mice brains …”
Section: Introductionmentioning
confidence: 99%
“… 25 27 In recent years, a number of studies have investigated the potential of PDT for treating AD by specifically targeting the Aβ peptide. 28 , 29 A range of photosensitizers have been tested, and these studies have shown that photo-oxidation of monomeric (or soluble) Aβ can inhibit the peptide’s aggregation and that photo-oxidation of fibrillar Aβ can cause fibril fragmentation and disintegration in vitro. 18 , 30 38 Encouragingly, Aβ aggregate degradation induced by photo-oxidation has also been found to attenuate aggregate toxicity 39 and reduce aggregate levels in the brains of AD mouse models.…”
Section: Introductionmentioning
confidence: 99%
“…Among the many approaches that have been studied, photodynamic therapy (PDT) has drawn the attention of researchers because it is spatiotemporally controllable and minimally invasive. , PDT has been used to treat diseases since the 1960s and is currently being used to treat many types of skin, lung, and esophageal cancers or pre-cancers . PDT requires a photosensitizer to produce singlet oxygens, which lead to the generation of reactive oxygen species (ROS) that subsequently oxidize cellular components, including cell membranes and organelles, and induce apoptosis, which destroys diseased tissues. In recent years, a number of studies have investigated the potential of PDT for treating AD by specifically targeting the Aβ peptide. , A range of photosensitizers have been tested, and these studies have shown that photo-oxidation of monomeric (or soluble) Aβ can inhibit the peptide’s aggregation and that photo-oxidation of fibrillar Aβ can cause fibril fragmentation and disintegration in vitro. , Encouragingly, Aβ aggregate degradation induced by photo-oxidation has also been found to attenuate aggregate toxicity and reduce aggregate levels in the brains of AD mouse models . In transgenic AD models of Caenorhabditis elegans, photo-oxidation of Aβ fibrils has been found to reduce Aβ neurotoxicity and extend the longevity of C.…”
Section: Introductionmentioning
confidence: 99%